Multimodal Approaches in English Language Teaching: Increasing Student's Skill in Communication in the Digital Era - Rini Marliana; Sulhairi (Asshika: Journal of English Language Teaching and Learning, 2024)
This study aimed to identify the factors contributing to students' nervousness when speaking English and assess their English proficiency at SMK Islam Plus Yadaro. This research employs qualitative methodologies with a descriptive orientation. Two instruments were employed in this study: the LFCAS questionnaire. The research sample consisted of 35 students divided into two classes: class X Accounting and class X TSM 2. The sample was obtained through purposive sampling. The data for this study were gathered by administering a questionnaire and a speaking test to two classes at SMK Islam Plus Yadaro: class X accounting and class X TSM 2. The results of the LFCAS questionnaire indicated that communication apprehension was 33.5%, fear of negative evaluation was 24.56%, and test anxiety was 41.94%. The results for the class X accounting and X TSM 2 students on the five aspects are as follows: Vocabulary (19.93%), Grammar (19.26%), Fluency (19.77%), Pronunciation (20.6%), and understanding (20.44%). The LFCAS questionnaire allows pupils to be classified as low or below average. In contrast, the students' speaking test results are classified as excellent.